Odpowiedź:
Szczegółowe wyjaśnienie:
Rozumiem, że chodzi o zadanie 4? Zatem:
a) 3 (x-2) + 4 (x-2) = (x-2) (3+4) = 7 (x-2) = 7x-14
b) 8 (x+4) - 5 (x+4) = (x+4) (8-5) = 3 (x+4) = 3x+12
c) 3 (x²-7) + 8(x²-7) = (x²-7) (3+8) = 11 (x²-7) = 11x² - 77
d) 7 (x-3) - (x-3) = (x-3) (7-1) = 6 (x-3) = 6x - 18
e) 4 (x+5) + 20 (x+5) = (x+5) (4+20) = 24 (x+5) = 24x + 120
f) 0,2 (-10+x) - (x-10) = 0,2 (x-10) - (x-10) = (x-10) (0,2-1) = -0,8 (x-10) = -0,8x + 8
Zadanie 3
a) (2x-3) - (x+5) + (x+4) = 2x-3 -x -5 +x +4 = 2x - 4 = 2 (x-2)
b) (3a-2) - (a+4) + (a-3) = 3a-2-a-4+a-3 = 3a - 9 = 3 (a-3)
c) 4 (2y-7y²) -3 (y²-3y) = 8y - 28y²-3y²+9y = -31y²+17y
d) -5 (2b+3z) + 2(2b-4z) = -10b - 15z + 4b - 8z = -6b - 23z